Effective photocatalysis of direct dyes under sunlight by silver, iron, and zinc nanoparticles doped on cotton. Issue 5 (October 2018) - Ali, Attarad; Gul, Ayesha; Ambreen, Sidra; Phull, Abdur Rehman; Zia, Muhammad
Abstract: Photo-oxidation processes assisted by nanomaterials are gaining attraction due to their potential applications. To explore reduction of organic pollutants by nanoparticles, this work was carried out using standard direct dyes that are frequently used in textile industries. The zinc, silver and iron NPs were separately impregnated on cotton to reduce the release in the water source. The selection of nanoparticles impregnated on cotton is based on photodynamic and photocatalytic capability of metals. The characterizations of composite materials revealed 11 to 26 nm particles size layered on cotton threads. Photocatalysis results indicate that nanoparticles impregnated on cotton exhibited remarkable photocatalytic activities under neutral pH condition. AgCt (Ag nanoparticles doped cotton) demonstrated maximum degradation of Orange-26 and Blue-199, 63 and 54%, respectively within 90 min. ZnCt (ZnO nanoparticles doped cotton) also showed good results (46 and 43% degradation) against two dyes. The photo-degradation of direct dyes were observed in the order as Orange-26 > Blue-199 > Green-26 > Fast-Pink > Yellow-44 > Red-80 > Violet-51 by AgCt. The study concludes that nanoparticles impregnated on cotton efficiently catalyze dyes under sunlight condition so can used for degradation of organic pollutants from wastewater.